Serum levels of galanin-like peptide and alarin are highly correlated with polycystic ovary syndrome - Mengchen Liu; Xueyu Zhang; Zihao Sun; Haoran Wang; Xianchang Sun; Wenjuan Zhang (Scientific Reports)
Abstract To compare the levels of galanin-like peptide (GALP) and alarin between patients with polycystic ovary syndrome (PCOS) and a control group, and to explore the correlations between GALP/alarin and PCOS. We selected a total of 103 PCOS patients and 89 non-PCOS control patients who visited the hospital during the same period. The PCOS patients and the controls were assigned by body mass index (BMI) into PCOS subgroup 1 and control subgroup 1 (18.5 < BMI < 24 kg/m2) and into PCOS subgroup 2 and control subgroup 2 (BMI ≥ 24 kg/m2). The general indices (weight, height, waist circumference, and hip circumference), serum sex hormone concentrations, biochemical indices, and GALP and alarin levels were measured for all subjects, and the differences in each index were compared between the two groups. (1) The BMI, waist-to-hip ratio (WHR), lipid accumulation product (LAP), total testosterone (total T), luteinizing hormone (LH) levels, fasting insulin (FINS), triglycerides (TG), alanine transaminase (ALT), HOMA-IR, and GALP and alarin concentrations were significantly higher and the AST/ALT ratio was significantly lower in the PCOS patients than in the controls. (2) Correlation analysis showed that serum GALP levels were positively correlated with BMI, WHR, LAP, total T, LH, FINS, TG, HOMA-IR, and alarin, and negatively correlated with AST/ALT. Serum alarin levels were correlated positively with BMI, WHR, LAP, total T, LH, FINS, TG, HOMA-IR, and GALP, and negatively with FSH and AST/ALT. Serum LAP, FINS, LH, and alarin were independent factors that influenced serum GALP levels, and serum FINS, LAP, LH, and GALP were independent factors that influenced serum alarin concentrations. The areas under the receiver operating characteristic curves (95% confidence intervals) for serum GALP and alarin levels in predicting PCOS were 0.78 (0.713, 0.847) and 0.828 (0.766, 0.889), respectively, and the cutoff values were 0.895 and 0.355, respectively. GALP and alarin were highly expressed in PCOS patients and closely associated with factors such as IR, HA, and obesity, and they showed favorable predictive values for PCOS.